2018
DOI: 10.1007/s00268-018-4533-x
|View full text |Cite
|
Sign up to set email alerts
|

The Results of In Situ Prosthetic Graft Replacement for Infected Aortic Disease

Abstract: In situ graft replacement of PIAAA and IASG is feasible with acceptable outcomes, but the outcome for IAPG is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Mortality rates up to 5e49% after in situ grafting versus 24e50% after extraanatomical bypass have been reported. 702,706,707,704,708 Infection related complications may occur in 0e20% after in situ grafts and older data suggest an equally high complication rate after extra-anatomical bypass, with the most feared being late aortic stump rupture in up to 20%. 321 No reliable comparative data exist between the various open surgical techniques.…”
Section: Mycotic Aaamentioning
confidence: 99%
“…Mortality rates up to 5e49% after in situ grafting versus 24e50% after extraanatomical bypass have been reported. 702,706,707,704,708 Infection related complications may occur in 0e20% after in situ grafts and older data suggest an equally high complication rate after extra-anatomical bypass, with the most feared being late aortic stump rupture in up to 20%. 321 No reliable comparative data exist between the various open surgical techniques.…”
Section: Mycotic Aaamentioning
confidence: 99%
“…Some researchers have advocated surgical protocols for infected AAA [ 9 13 ]. We have previously reported our principles for treating infected aortic disease, including primary infected AAA, infected aortic prosthetic grafts, and infected aortic stent grafts [ 10 11 ]. These studies showed favorable outcomes for in situ prosthetic graft bypasses with omental wrappings [ 10 11 19 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported our principles for treating infected aortic disease, including primary infected AAA, infected aortic prosthetic grafts, and infected aortic stent grafts [ 10 11 ]. These studies showed favorable outcomes for in situ prosthetic graft bypasses with omental wrappings [ 10 11 19 20 ]. We applied the same surgical principles to all cases of infected stent grafts in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal strategy is supposed to rebuild the trunk of artery to maximize blood supply for limb salvage. In situ arterial reconstruction often failed to restore aortic blood ow in the setting of infected groin, which was attribute to uncontrolled infection and erosion-related bleeding 11,12 . In this regard, the bypass strategy was proposed.…”
Section: Discussionmentioning
confidence: 99%